2007
DOI: 10.1096/fj.06-7756com
|View full text |Cite
|
Sign up to set email alerts
|

Astroglia‐derived retinoic acid is a key factor in glia‐induced neurogenesis

Abstract: Astroglial cells are essential components of the neurogenic niches within the central nervous system. Emerging evidence suggests that they are among the key regulators of postnatal neurogenesis. Although astrocytes have been demonstrated to possess the potential to instruct stem cells to adopt a neuronal fate, little is known about the nature of the glia-derived instructive signals. Here we propose that all-trans retinoic acid, one of the most powerful morphogenic molecules regulating neuronal cell fate commit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 51 publications
(73 reference statements)
6
65
1
Order By: Relevance
“…It has been previously demonstrated that RALDH enzymes are expressed in primary rodent cultured astrocytes (Kornyei et al, 2007;McCaffery et al, 2004;Wang et al, 2011). This study, however, demonstrates that this expression is not reflected in the majority of astrocytes in vivo either in the mouse or in the human.…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…It has been previously demonstrated that RALDH enzymes are expressed in primary rodent cultured astrocytes (Kornyei et al, 2007;McCaffery et al, 2004;Wang et al, 2011). This study, however, demonstrates that this expression is not reflected in the majority of astrocytes in vivo either in the mouse or in the human.…”
Section: Discussioncontrasting
confidence: 59%
“…This study, however, demonstrates that this expression is not reflected in the majority of astrocytes in vivo either in the mouse or in the human. Thus, although it has been previously proposed that astrocytes in the rodent may provide RA for neural progenitors in the brain (Kornyei et al, 2007) and for neurons in the hippocampus (Wang et al, 2011), it is unlikely that these are a major source of RA under normal circumstances. The low levels of RALDH protein and mRNA in the adult mouse brain are corroborated by the weak in situ hybridization signal evident from results documented in the Allen Brain Atlas (http://mouse.brainmap.org/).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations